How to pass Standard Grade geography in full colour - Dick, Bill (How to pass, 2010)
How to Pass is the Number 1 revision series for Scottish qualifications across the three examination levels of Standard Grade, Intermediate and Higher! Second editions of the books present all of the material in full colour for the first time. How to Pass Standard Grade Geography provides a comprehensive guide to the course offered by the Scottish Qualifications Authority, and whilst no book can guarantee an examination pass, this title combines an overview of the course syllabus and exam requirements, as well as a guide to revision techniques and advice on sitting the examination itself. Like all titles in the How to Pass series, it offers unique insights into what markers are actually looking for, so that users of this book will avoid unnecessary mistakes - and should gain those extra marks that are so essential to moving up a grade ...